Ultraselective Carbon Nanotubes for Photoacoustic Imaging of Inflamed Atherosclerotic Plaques. (17th June 2021) - Gifani, Mahsa; Eddins, Devon J.; Kosuge, Hisanori; Zhang, Yapei; Paluri, Sesha L. A.; Larson, Timothy; Leeper, Nicholas; Herzenberg, Leonore A.; Gambhir, Sanjiv Sam; McConnell, Michael V.; Ghosn, Eliver E. B.; Smith, Bryan Ronain
Abstract: Disruption of vulnerable atherosclerotic plaques often leads to myocardial infarction and stroke, the leading causes of morbidity and mortality in the United States. A diagnostic method that detects early‐stage high‐risk atherosclerotic plaques could prevent these sequelae. The abundant immune cells in the arterial wall, especially inflammatory Ly‐6C hi monocytes and foamy macrophages, are indicative of plaque inflammation, and may be associated with plaque vulnerability. Hence, a new method is sought to develop that specifically targets these immune cells to offer clinically relevant diagnostic information about cardiovascular disease. Ultraselective nanoparticle targeting of Ly‐6C hi monocytes and foamy macrophages and clinically‐viable photoacoustic imaging (PAI) are combined in order to precisely and specifically image inflamed plaques ex vivo in a mouse model that mimics human vulnerable plaques histopathologically. Within the plaques, high‐dimensional single‐cell flow cytometry (13‐parameter) shows that the nanoparticles are almost‐exclusively taken up by the Ly‐6C hi monocytes and foamy macrophages that heavily infiltrate plaques. PAI identifies inflamed atherosclerotic plaques that display ≈6‐fold greater signal compared to controls ( P < 0.001) 6 h after intravenous injection of ultraselective carbon nanotubes, with in vivo corroboration via optical imaging. This highly‐selective strategy may provide a targeted, noninvasive imaging strategy to accurately identify and diagnose inflamed atherosclerotic lesions. Abstract : Vulnerable atherosclerotic plaques may lead to heart attacks. Inflammation, including infiltration of inflammatory monocytes/macrophages, characterizes such plaques. This study leverages the nanoparticles' unprecedented selectivity to inflammatory monocytes/macrophages. These nanoparticles specifically detect inflamed plaques using photoacoustic imaging of atherosclerotic mouse arteries, corroborated by high‐dimensional flow cytometry and optical imaging. This highly selective strategy may accurately identify and diagnose inflamed atherosclerotic lesions.